Wybrane psychologiczne i socjologiczne aspekty przedsiębiorczości wiejskiej - Sikorska-Wolak, Izabella; Krzyżanowska, Krystyna (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2002)
In this paper a theoretical framework of entrepreneurship and its relationship with innovations are presented. Psychological and sociological aspects of rural entrepreneurship are particularly highlighted. The differences in needs and activity motivations between entrepreneurs and other people were distinguished. Additionally, the set of features specific for entrepreneurs was identified. Considering sociological attitude, there was discussed the role of leaders - particularly those of producer groups - in the development of entrepreneurship in rural areas. The leaders' personalities, functions they actually fulfill and their potential for rural community were also recognised.